Preliminary evidence of a potential reproductive aggregation area of the common stingray Dasyatis pastinaca (Linnaeus, 1758) (Chondrichthyes – Dasyatidae) in the Central Mediterranean Sea - GRANCAGNOLO, DESIRÉE; CATTANO, CARLO; QUATTROCCHI, FEDERICO; MILAZZO, MARCO (Mediterranean Marine Science, 2023)
Shallow and coastal aggregations of batoids are poorly documented in the Mediterranean Sea, despite being likely threatened by multiple anthropogenic pressures. We report the first observations of a potential summer reproductive aggregation of the common stingray (Dasyatis pastinaca). The recurrent presence in previous years of several pregnant females, a mature male and a female with fresh bite wounds was recorded in shallow waters by recreational scuba divers and scientists in Scilla Bay (Strait of Messina, Italy), a location with unique oceanographic features in the Central Mediterranean Sea. These observations suggest that the area could be used as a parturition and mating site in early summer, and this is significant for the conservation of this Vulnerable species.